Associations of Sodium and Potassium with Obesity Measures Among Diverse US Hispanic/Latino Adults: Results from the Hispanic Community Health Study/Study of Latinos. Issue 2 (10th January 2018) - Elfassy, Tali; Mossavar‐Rahmani, Yasmin; Van Horn, Linda; Gellman, Marc; Sotres‐Alvarez, Daniela; Schneiderman, Neil; Daviglus, Martha; Beasley, Jeannette M; Llabre, Maria M.; Shaw, Pamela A.; Prado, Guillermo; Florez, Hermes; et al.
Abstract : Objective: The objective of this study was to evaluate cross‐sectional associations of sodium and potassium with BMI, waist circumference (WC), and body fat and to determine whether the nativity and/or duration of United States (US) residence modified these associations. Methods: Sodium and potassium were derived from 24‐hour diet recalls from 16, 156 US participants of the 2008 to 2011 Hispanic Community Health Study/Study of Latinos (HCHS/SOL) and from 24‐hour urine in 447 HCHS/SOL participants. BMI, WC, and body fat were measured. Results: Dietary sodium that was 500 mg/d higher was cross‐sectionally associated with a 0.07‐kg/m 2 higher BMI ( P  < 0.05) and a 0.18‐cm larger WC ( P  = 0.04). Dietary potassium that was 500 mg/d higher was only associated with lower BMI and smaller WC among those who were foreign‐born with 10 + years in the US (−0.13 kg/m 2, P  < 0.01 and −0.36 cm, P  = 0.01, respectively) and among those who were US‐born (−0.62 kg/m 2, P  < 0.01 and −1.42 cm, P  < 0.01, respectively). Urinary sodium that was 500 mg/d higher was associated with a 0.27‐kg/m 2 higher BMI ( P  < 0.01) and 0.54 kg more body fat ( P  < 0.01). Conclusions: Sodium intake was associated with higher BMI, WC, and body fat. Potassium intake was associated with lower BMI and smaller WC among US‐born participants and participants with a longer duration of US residence.